2014
DOI: 10.1016/j.str.2013.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of the Autophagy-Related LC3/Atg13 LIR Complex: Recognition and Interaction Mechanism

Abstract: Autophagy is a bulk degradation pathway that removes cytosolic materials to maintain cellular homeostasis. The autophagy-related gene 13 (Atg13) and microtubule associate protein 1 light chain 3 (LC3) proteins are required for autophagosome formation. We demonstrate that each of the human LC3 isoforms (LC3A, LC3B, and LC3C) interacts with Atg13 via the LC3 interacting region (LIR) of Atg13. Using X-ray crystallography, we solved the macromolecular structures of LC3A and LC3C, along with the complex structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(113 citation statements)
references
References 50 publications
(55 reference statements)
3
110
0
Order By: Relevance
“…[46][47][48] Other core members of the autophagy machinery, Atg3, Atg32 in yeast or ATG4B, ATG7, and ATG13 in mammals, undergo LIR-dependent interactions with LC3 that potentially contribute to autophagy regulation. 17,21,22,[49][50][51] Moreover, some vesicle trafficking proteins, such as the RAB7-interacting protein FYCO1 or the GAP TBC1D5, interact with LC3 and play critical roles in intracellular trafficking of autophagosomes in a LIR-dependent manner. 52,53 Based on our data, interaction between PEBP1 and LC3 via the LIR motif might regulate the accessibility of free LC3 proteins for conjugation to PE, which is a critical step necessary for autophagosome biogenesis (depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] Other core members of the autophagy machinery, Atg3, Atg32 in yeast or ATG4B, ATG7, and ATG13 in mammals, undergo LIR-dependent interactions with LC3 that potentially contribute to autophagy regulation. 17,21,22,[49][50][51] Moreover, some vesicle trafficking proteins, such as the RAB7-interacting protein FYCO1 or the GAP TBC1D5, interact with LC3 and play critical roles in intracellular trafficking of autophagosomes in a LIR-dependent manner. 52,53 Based on our data, interaction between PEBP1 and LC3 via the LIR motif might regulate the accessibility of free LC3 proteins for conjugation to PE, which is a critical step necessary for autophagosome biogenesis (depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The five genes were then digested with SacI and HindIII (New England Biolabs) restriction enzymes and subcloned into the pET30⌬S.E. expression vector (28), purified using an agarose DNA extraction kit (Roche Applied Science), and ligated with T4 DNA ligase at 20°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Human ATG13 also contains a LIR motif [55]. The crystal structures of the ATG13 LIR bound to LC3A, B, and C have recently been determined [56]. The structure showed that the FVMI peptide sequence of ATG13 binds in an essentially identical manner to the corresponding WTHL peptide of p62.…”
Section: Structural Aspects Of Ulk1 Complex Componentsmentioning
confidence: 99%